Selection of IgG Variants with Increased FcRn Binding Using Random and Directed Mutagenesis: Impact on Effector Functions - Monnet, Céline; Jorieux, Sylvie; Urbain, Rémi; Fournier, Nathalie; Bouayadi, Khalil; De Romeuf, Christophe; Behrens, Christian K.; Fontayne, Alexandre; Mondon, Philippe (Frontiers in Immunology, 2015)
Despite the reasonably long half-life of IgGs, market pressure for higher patient convenience while conserving efficacy continues to drive IgG half-life improvement. IgG half-life is dependent on the neonatal Fc receptor FcRn, which amongst other functions, protects IgG from catabolism. FcRn binds the Fc domain of IgG at an acidic pH ensuring that endocytosed IgG will not be degraded in lysosomal compartments and will then be released into the bloodstream. Consistent with this mechanism of action, several Fc engineered IgG with increased FcRn affinity and conserved pH-dependency were designed and resulted in longer half-life in vivo in human FcRn transgenic mice (hFcRn), cynomolgus monkeys and recently in healthy humans. These IgG variants were usually obtained by in silico approaches or directed mutagenesis in the FcRn binding site. Using random mutagenesis, combined with a pH-dependent phage display selection process, we isolated IgG variants with improved FcRn-binding which exhibited longer in vivo half-life in hFcRn mice. Interestingly, many mutations enhancing Fc/FcRn interaction were located at a distance from the FcRn binding site validating our random molecular approach. Directed mutagenesis was then applied to generate new variants to further characterize our IgG variants and the effect of the mutations selected. Since these mutations are distributed over the whole Fc sequence, binding to other Fc effectors, such as complement C1q and FcgRs, was dramatically modified, even by mutations distant from these effectors’ binding sites. Hence, we obtained numerous IgG variants with increased FcRn binding and different binding patterns to other Fc effectors, including variants without any effector function, providing distinct “fit-for-purpose” Fc molecules. We therefore provide evidence that half-life and effector functions should be optimized simultaneously as mutations can have unexpected effects on all Fc receptors that are critical for IgG therapeutic efficacy.